Аппаратурно-программный комплекс первичной обработки данных радиометрической системы «Зір» - Shylo, S. A.; Bychkov, D. M.; Havrylenko, A. S. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper discusses the structure, functional features, and parameters of the hardware‑software complex for primary data processing of the radiometric system designed to obtain radiothermal images of humans for use by security and customs services.